Solid-liquid interfacial energy of solid succinonitrile solution in equilibrium with succinonitrile-neopentylglycol eutectic liquid - Karadag, Saadet B.; Altintas, Yemliha; Ozturk, Esra; Aksoz, Sezen; Keslioglu, Kazim; Marasli, Necmettin (ELSEVIER, 2013)
The grain boundary groove shapes for solid succinonitrile solution (SCN-5 mole% NPG) in equilibrium with the succinonitrile (SCN)-neopentylglycol (NPG) eutectic liquid (SCN-9.55 mole% NPG) have been directly observed by using a horizontal linear temperature gradient apparatus at 317.1 K equilibrium temperature. From the observed grain boundary groove shapes, the Gibbs-Thomson coefficient (Gamma) and solid-liquid interfacial energy (sigma(SL)) of solid SCN solution have been determined to be (5.43 +/- 0.50) x 10(-8) K m and (8.09 +/- 1.21) x 10(-3) J m(-2), respectively. The grain boundary energy of solid SCN solution has been determined to be (14.22 +/- 2.28) x 10(-3) J m(-2) from the observed grain boundary groove shapes. The thermal conductivity for SCN-9.55 mole% NPG eutectic solid phase and the thermal conductivity ratio of eutectic liquid phase to eutectic solid phase at the melting temperature have also been measured with a radial heat flow apparatus and Bridgman type growth apparatus, respectively. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Interfaces; Phase equilibria; Surface properties; Organic compounds; SURFACE ENERGIES; ORGANIC ALLOYS; AL-CU; MELT; SOLIDIFICATION; ANISOTROPY; GROWTH; TENSION; SYSTEMS; METALS; Crystallography; Materials Science; Physics